Infrared absorption cross sections for propene broadened by N2 (450–1250 cm−1) and by H2 (2680–3220 cm−1). (February 2023) - Bernath, Peter F.; Dodangodage, Randika; Zhao, Jianbao; Billinghurst, Brant
Highlights: High resolution Fourier transform spectroscopy of propene at 202–295 K. Infrared absorption cross sections of propene broadened by N2 for 450–1250 cm −1 region. Infrared absorption cross sections of propene broadened by H2 for 2680–3220 cm −1 region. Data are useful for planetary atmospheres including giant planets and Titan. Abstract: Propene (C3 H6 ) has been measured in the planetary atmospheres of Earth and Titan, and may be detected in the giant planets by infrared spectroscopy. Propene infrared absorption cross sections have been determined in the 2680–3220 cm −1 and 450–1250 cm −1 regions by high-resolution Fourier transform spectroscopy with H2 and N2, respectively, as broadening gases. Samples of propene were held at 202, 232, 265, 297 K.